Effects of Solanum nigrum L. extract and its main glycoalkaloids on selected tissues of Tenebrio molitor L. as factors increasing the toxicity of fenitrothion insecticide - Spochacz, Marta (My University, 2021)
During the research, the influence of the black nightshade (Solanum nigrum) unripe fruit extract and its main glycoalkaloids on selected physiological aspects of a yellow mealworm (Tenebrio molitor) was checked for potential usage against this pest. As a next step, the toxic concentrations of fenitrotion (LC50 and LC40) were calculated for the description of the influence of the S. nigrum extract on the toxicity of fenitrothion in two strategies of application. In the first strategy, the extract was mixed with fenitrothion in the ratio 1:1 and applied to the larvae, and in the second strategy, the extract was given 24 h before fenitrothion application. The results showed, that the S. nigrum extract causes sublethal effects such as changes in the activity of visceral muscles, changes in the concentration of stored biomolecules, and disturbances in the midgut and fat body cells in T. molitor. Glycoalkaloids present in the S. nigrum extract cause sublethal toxic effects in yellow mealworm. The differences in the effects caused by the extract and single glycoalkaloids indicate the cooperative action of both glycoalkaloids. The S. nigrum extract applied at the same time with fenitrothion did not increase the lethality of T. molitor larvae comparing to the effects caused by fenitrothion, however, it caused sublethal effects. Appropriate correlation of the S. nigrum extract application before fenitrothion caused significant increase of T. molitor mortality and strengthen the sublethal effects.

W niniejszej rozprawie doktorskiej zbadany został wpływ ekstraktu z niedojrzałych owoców psianki czarnej (Solanum nigrum) oraz jego dwóch głównych glikoalkaloidów na wybrane aspekty fizjologii szkodnika magazynów zbożowych, mącznika młynarka (Tenebrio molitor) pod kątem możliwości wykorzystania go w zwalczaniu tego owada. Następnie określono wpływ ekstraktu na toksyczność fenitrotionu (LC50 i LC40) w dwóch strategiach aplikacji. W pierwszej ekstrakt został podany w mieszaninie z fenitrotionem w proporcji 1:1, natomiast w drugiej, ekstrakt został podany na 24 h przed aplikacją fenitrotionu. Otrzymane wyniki wskazały, że ekstrakt z S. nigrum powoduje u mącznika młynarka efekty subletalne, takie jak zmiany w kurczliwości narządów wewnętrznych, zmiany zawartości zmagazynowanych biocząsteczek i zaburzenia w ultrastrukturze komórek jelita środkowego i ciała tłuszczowego. Glikoalkaloidy obecne w ekstrakcie powodują subletalne efekty toksyczne, a różnice w ich działaniu z ekstraktem, wskazują na synergistyczne działanie glikoalkaloidów. Ekstrakt z S. nigrum podawany równocześnie z fenitrotionem nie zwiększa śmiertelności larw, w porównaniu do efektów powodowanych przez sam fenitrotion, jednak widoczne są efekty subletalne. Odpowiednio skorelowane podanie ekstraktu z psianki czarnej przed aplikacją fenitrotionu, spowodowało istotny wzrost śmiertelności T. molitor i nasiliło efekty subletalne.
Działanie ekstraktu z Solanum nigrum L. i jego głównych glikoalkaloidów, jako czynników zwiększających toksyczność insektycydu fenitrotionu w wybranych tkankach Tenebrio molitor L.
Wydział Biologii
Keywords: Solanum nigrum extract; glycoalkaloids; fenitrothion; Tenebrio molitor; ultrastructure; ekstrakt z Solanum nigrum; glikoalkaloidy; fenitrotion; ultrastruktura